COMPARATIVE STUDY BETWEEN TRAMADOL AND KETOROLAC IN POST-OPERATIVE ANALGESIA IN CHOLECYSTECTOMY IN A TERTIARY CARE HOSPITAL - KAUSHIK, SHOBHIT; RAI, JAYANT; HARSHWARDHAN; KAUSHIK, SHIPRA (International Journal of Current Pharmaceutical Research, 2023)
Objective: The aim of the study is to compare the analgesic efficacy of Tramadol (TRA) to that of Ketorolac (KET) administered I. V. and at fixed times over 24 h after open cholecystectomy. Methods: The study enrolled 50 ASA I and II patients between 30-60 y of age of either sex undergoing open cholecystectomy. Two treatment groups were formed with 25 patients in each group which received Tramadol and Ketorolac. The pain score was measured using Visual Analog Scale (VAS). Results: Statistical analysis was done by t-test, in which onset of action, duration of action, number of rescue analgesics required and VAS score was compared. Conclusion: Tramadol is better analgesic than Ketorolac.